Soil fertility evaluation based on the sugeno fuzzy logical model - Ziyadullaev Davron; Mukhamedieva Dilnoz; Xoliyorov Umirzoq; Shanasirova Nodira; Hudayberdiyev Ulmasjon; Eshmuradov Dilshod; Dzholdasbaeva Aksulu (BIO Web of Conferences, 2023)
With the improvement of soils, the productivity of agricultural crops and the efficiency of mineral fertilizers increase; though for individual types of fertilizers the changes take different ways. In different types of soil, different interactions between soil and fertilizersare observed;variouscrop varieties react differently to them, because each variety was bred under one of these interaction conditions, and its influence is phenotypically fixed in it. It was established that the fertility of different types of soils is quantitatively best characterized bystored soil moisture, bulk density, and it is closely related to such generally recognized fertility components as the amount of humus, nitrogen, phosphorus, etc. The main aim of the article is to build a Sugeno fuzzy logical model for assessing soil fertility.